Quality of life in patients with chronic back pain - Haluzíková, Jana; Wieclawová, Gabriela (Profese Online, 2020)
Background: Back pain often recurs in patients or becomes chronic. It can cause long-term incapacity for work and hamper resuming of work. Pain is a complex experience with an impact on biopsychosocial and economic levels. Pain also influences mobility and quality of life. Aim: The present paper aimed at measuring the quality of life in patients with chronic back pain. Further objectives were to determine if pain intensity was reduced during pharmacotherapy and if pain intensity has an impact on the quality of life. Methodology: The SF-36 questionnaire was employed to assess the quality of life and VAS to assess pain. Results: He results of this survey indicate that patients with chronic back pain have the lowest values in physical role functioning subscales, i.e., their health status entails limitations at work or during the performance of activities of daily living. The second lowest value was that of the bodily pain subscale, imposing limitations on both household and workplace. Surprisingly, the mental health values were higher than the physical functioning values. Depression, pessimism, sadness or nervousness were often not perceived by the respondents, rather, they felt tired and weak. Mean pain intensity before treatment in both sexes was 7.5 VAS. There was no major decrease in pain intensity during treatment. Conclusion: Pain intensity has an impact on the quality of life. The results show that pain has an influence on both physical and mental health. The respondents were often limited in various working activities or could do less than desired. Respondents reported equal or poorer health status compared to the status a year before. Pharmacotherapy did not result in pain.
Keywords: quality of life; chronic pain; back; Visual Analogue Scale; SF-36 scale; physical health; mental health